KEANEKARAGAMAN BURUNG DAN MAMALIA PADA LAHAN REKLAMASI PT. ANEKA TAMBANG BOGOR, JAWA BARAT - Ratna Sari Hasibuan; Tun Susdiyanti; Fauzi Septiana (EKOLOGIA, 2018)
PT. Aneka Tambang has reclaimed land due to gold production activities. Reclamation land is a process whereby the damaged land is repaired to its natural state. Indicators of succession can be showed in the presence of plants and animals. Birds are a good indicator for assessing biodiversity in a region, because can occupy a large habitat of near the top of the food chain. The spread of plant seeds can be done by birds and mammals through its feces. Identification and observation of bird and mammal diversity can be used to improve the conservation of birds and mammals in the area. The purpose of this research was to study the diversity of birds and mammals. The method used were Indices Ponctuels dAbondance(IPA) method for birdwatching and transect lines for mammalian observation. Result showed 33 speciesof birds and 9 species of mammals were found in this study. The bird species was dominated by the Cucak Kutilang type and the mammal was dominated by Squirrel Kekes.Key words : PT. Aneka Tambang, diversity ,bird ,mammal